Northwest history. Mining. Mines reopened. 1922-05-03 (1922)
To resume work at giant mine. - Supplies are being taken this week to the property of the Giant Mining and Development company on Beaver creek in the Coeur d'Alenes, where work is to be resumed at once. The south drift is to be continued to intersect the main ledge, according to Paul Lever, manager.